Huntington and the liberal thought. Problems of Anglo-democracy to understand politics - Korstanje, Maximiliano (Nómadas. Critical Journal of Social and Juridical Sciences, 2013)
The liberal thought has inspired philosophy and sociology during years. From its view, US has two main goals. One is to expand the civilized culture to other non-western countries, and second to grant the democratic values. Paradoxically, terrorism poses one of the most troubling aspects of contemporanean democracy. On one hand, not only it defies the democratic resources to anticipate the next blow, but also put US to conduct one-sided attacks to autonomous countries. To legitimize the expansion of this new imperial order, the liberal discourse appealed to two strategies: first and foremost, denoting pejoratively as the case of Latin America that there is a cultural matrix that impedes these countries to embrace democracy. Secondly, it evidences the own myopia and ignorance to understand terrorism and politics. Our thesis is that US and England practiced a distortion of Democracy to colonize the world, the Anglo-democracy. As a social construe, democracy was conducive to the protection of status quo´s interests